The memory of Modernist poetry - Coelho, Eduardo (Estudos Avançados, 2022)
In the 1920s, the Brazilian modernisms revealed strategies not only for the rupture with the tradition but also for continuity, as their relations both with the coffee-based aristocratic elite (which sponsored of the Modern Art Week) and with Romanticism (especially José de Alencar’s). The construction of a Modernist memory about Brazil is one of the most revealing indices of this ambivalent movement of rupture with and continuity of tradition, highlighting, in this process, the history of violence in colonial Brazil, as well as the incorporation of a Brazilian way of speaking through literature.